Kebijakan Pemerintah Indonesia dan Thailand dalam Penanggulangan HIV AIDS - Kurniawan, Fajar; Lisnawati; Tawakkal; Nurmala, Ira; Nasus, Evodius (PT. Banjarese Pacific Indonesia, 2023)
Introduction: WHO's global health sector strategy 2022–2030 on HIV goals to reduce HIV infections from 1.5 million by 2020 to 335,000 by 2030, and deaths from 680,000 in 2020 to below 240,000 by 2030. The Southeast Asia Regional Action Plan (RAP) for HIV (2017–2021) provides a clear vision of